A clinicopathological study of adnexal masses in the tertiary care hospital, Kadapa - Bandi, Sowjanya; Thulamandi, Lakshmi Suseela; Eka, Sowjanya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Adnexal mass is a common clinical presentation among women of all age groups and is extremely common among reproductive age groups. It may be gynecological or non-gynecological origin. The exact prevalence of adnexal mass could not be determined, as most of them develop and resolve without any clinical symptoms. Adnexal mass poses a special perplexity to the attending gynecologists, because the differential diagnosis is extensive and most masses are benign. Differential diagnosis of adnexal mass is complex and includes benign and malignant ovarian tumors, functional cysts, para ovarian cysts, tubo-ovarian abscess, ectopic pregnancy, hydrosalpinx, fimbrial cyst, tubal malignancies, broad ligament fibroid. Methods: It was a prospective study conducted in the department of gynecology, GGH, Kadapa. It was a tertiary care hospital. Total of hundred cases were included in the study based on selection criteria. Ethical committee approval was taken prior to the study. Results: A total 100 cases of adnexal masses were included in the study. 40% of study subjects had parity 2 and 11% had maximum parity 4. 81% of study subjects had surgical management. 45 patients had CA125 >35 u/ml. Among them 48% have benign lesions and 51% have malignant lesions. 92.72% of patients with CA125 <35 u/ml have benign lesions and 7.27% have malignant lesions. Conclusions: Adnexal mass was found to be more common in middle females (54%) in age group 31-50 years. Serous cystadenoma and simple serous cyst (25%) were common benign lesions and most common malignant lesion was serous cystadenocarcinoma.